Usability heuristic evaluation in Ambient Assisted Living ecosystems - Romeiro, Carlos (2020)
In the past few years there has been a significant growth of the elderly population in both developing and developed countries. This event provided new economic, technical and demographic challenges to current societies in several areas and services. Among them the healthcare services can be highlighted, due to its impact in people daily lives. As a natural response an effort has been made by both the scientific and industrial community to develop alternatives, which could mitigate the current healthcare services bottlenecks and provide means in aiding and improve the end-user life quality. Through a combination of information and communication technologies specialized ecosystems have been developed, however multiple challenges arose, which compromise their adoption and acceptance among the main stakeholders, such as their autonomy, robustness, security, integration, human-computer interactions and usability. As consequence an effort has been made to deal with the technical related bottlenecks, which shifted the development process focus from the end-user to the ecosystems technological impairments. Despite there being user related issues, such as usability, which still remains to be addressed. Therefore this article focuses over the ecosystem’s usability through the analysis of the process used to check the ecosystem’s compliance level with the usability guidelines from Jakob Nielsen and Shneiderman; and the identification of the quantifiable parameters for each principle that could aid in the heuristics evaluation process by maximizing its objectivity improve its overall accuracy.